Impact of labor, FDI and R&D on business sustainability - Dan Costin Nitescu; Valentin Murgu; Elena Diana Căpriță (Amfiteatru Economic Journal, 2019)
The research addresses the problem of identifying the impact of the labor force, of the investments and the research and development on the direction of the long-term growth strategy, in order to achieve the business sustainability of some countries of the European Union. The paper addresses the main challenges and macroeconomic developments at European level, as well as, relevant aspects reflected in some research, representative studies for the analysed issues. It also includes the empirical study conducted for 24 European countries, over a 22-year period, in which, based on the use of the multiple regression model, we analysed the correlations between the Export and Import indicators - endogenous variables, considered to be the promoters of business sustainability, and the macroeconomic indicators Labour force, FDI (Foreign Direct Investment) and R&D - exogenous variables. In the short term, the research reflects the fact that the two indicators R&D expenditures and the number of researchers have a statistically significant positive impact on the exports of the states. In addition, the participation of the Labor force and FDI helps to increase the share of exports in GDP, too. According to the results of the research, the advanced economies register a benefit in the export activity, supported also by the large number of researchers, involved in the research and development activity. In the long term, R&D expenses and Labor force participation have a bigger impact on exports compared to other factors taken into account, given that the level of unemployment in an economy does not have a significant impact on foreign trade. Our work adds value to existing research by addressing the issue of evaluating the impact of innovation (through the variables: research and development expenses, researchers involved in research and development, patent applications - nonresidents and patent applications - residents), of labor force (through the variables: labor and unemployment - % of total labor force) and of investments (through the variable: foreign direct investment) on foreign trade of some countries of the European Union.
Keywords: C23; O11; O47; O52; Q56; 330; business sustainability; innovation; labor force; investment; research - development; export; import; European Union (EU)